2019
DOI: 10.1007/s00464-019-06732-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis in a randomized trial of early closure of a temporary ileostomy after rectal resection for cancer (EASY trial)

Abstract: Background Hospital costs associated with the treatment of rectal cancer are considerable and the formation of a temporary stoma accounts for additional costs. Results from the EASY trial showed that early closure of a temporary ileostomy was associated with significantly fewer postoperative complications but no difference in health-related quality of life up to 12 months after rectal resection. The aim of the present study was to perform a cost analysis within the framework of the EASY trial. Methods Early cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Within the cohort, we report a high rate of loop ileostomy-related SBO with various causes both before and after closure, which together with other negative ileostomy-related outcomes, such as poorer functional outcomes and costs, raises concern about the routine use of loop ileostomy [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the cohort, we report a high rate of loop ileostomy-related SBO with various causes both before and after closure, which together with other negative ileostomy-related outcomes, such as poorer functional outcomes and costs, raises concern about the routine use of loop ileostomy [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the cost perspective, Park and colleagues found that there was a significant reduction in the mean cost of early stoma closure of USD 4060 compared to late closure 43 . The cost savings stemmed mostly from there being fewer reoperations, readmissions and endoscopic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]8,[16][17][18][19][20][21][22] In addition, prolonged time to closure (more than 6 months) of temporary stomas was found to increase the risk of complications and the length of hospital stay, subsequently worsens the patients' quality of life and raising hospital costs. [6][7][8] Understanding risk factors for the development of these complications would aid in targeting them for preventive measures thus, improve patients' outcomes. As the time to stoma closure is considered an important predictor for complications, determining the factors which prolong the time to closure is important.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In addition, prolonged time to closure (more than 6 months) of temporary stomas was found to increase the risk of complications and the length of hospital stay, subsequently worsens the patients' quality of life and raising hospital costs. [6][7][8] Given the implications of prolonged time to stoma closure, identifying risk factors which prolong the time to closure would aid in targeting them for preventive measures. Therefore, this study was conducted to determine risk factors that affect the time to stoma closure and identify predictors of stoma-closure complications among ostomy patients at our institute.…”
Section: Introductionmentioning
confidence: 99%